Unlikely downsizers: The prison service's role in reversing mass incarceration in Kazakhstan - Slade, Gavin (Theoretical criminology, 2023)
Since 2000, the prison rate has declined significantly in Kazakhstan. This article demonstrates that the Kazakhstani prison service, counterintuitively, became a key advocate of prison downsizing owing to a coalescence of norms and incentives in the 1980s and 1990s. In the process, the prison service elite maintained the loyalty of rank-and-file personnel through a focus on reform to performative and quantifiable measures of penal performance – such as rankings in the World Prison Brief – while qualitative changes to the service's identity and organization remained unchanged. Prison staff remained militarized and their livelihood and professional culture continued to be independent of the existence of prisons. In conclusion, we argue that the Kazakhstani case demonstrates the need for an integrative theory of penal change that focuses on the interplay of macro-, meso- and micro-level factors in relationally shaping the norms, incentives and opportunities of penal policy actors.